2009
DOI: 10.1155/2009/949315
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Endoscopic Adenoidectomy

Abstract: Objective. Adenoid curette guided by an indirect transoral mirror and a headlight is a simple and quick procedure that has already been in use for a long time, but this method carries a high risk of recurrence unless done by a well-experienced surgeon. The purpose of this paper was to evaluate the efficacy of transoral endoscopic adenoidectomy in relieving the obstructive nasal symptoms. Methods. 300 children underwent transoral endoscopic adenoidectomy using the classic adenoid curette and St Claire Thomson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Therefore it takes part in the pathogenesis of rhinosinusitis, recurrent otitis media (OM), and OM with effusion. [11] The causes of adenoid hypertrophy are not fully known. Some of the triggers that have been associated with symptomatic enlargement of adenoidal tissue include microbial stimuli and external irritants such as cigarette smoke.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…Therefore it takes part in the pathogenesis of rhinosinusitis, recurrent otitis media (OM), and OM with effusion. [11] The causes of adenoid hypertrophy are not fully known. Some of the triggers that have been associated with symptomatic enlargement of adenoidal tissue include microbial stimuli and external irritants such as cigarette smoke.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…They concluded that digital palpation is not a reliable method and visualization of the nasopharynx is important for a complete adenoidectomy. El-Badrawy and M. Abdel-Aziz [2] performed transoral endoscopicguided adenoidectomy using the adenoid curette and forceps similar to our first group of patients. Wan et al [5] performed nasal endoscopic-guided adenoidectomy using a classic adenoid curette.…”
Section: Discussionmentioning
confidence: 92%
“…Adenoidal hypertrophy is a common cause of airway obstruction in children and can cause symptoms such as nasal discharge, mouth breathing, nasal obstruction, snoring, sleep apnea, hyponasal speech, orofacial growth disturbance, otitis media with effusion, recurrent otitis media and rhinosinusitis [1][2][3]. Adenoidectomy is often indicated in patients with these complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Buchinsky et al [20] found no re-growth in children following adenoidectomy, while Emerick and Cunningham [3] attributed the cause of recurrent symptoms after adenoidectomy to recurrent or residual adenoid, and/or tubal tonsil hypertrophy. Also, recurrent upper respiratory tract infections after adenoidectomy may play a role in recurrence of AH [3,12], a point that was not taken into our consideration during the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Yanagisawa and Weaver [11] used the same technique with endoscopic vision but they found difficulty in maneuvering the microdebrider tip into the nasopharynx. Trans-oral endoscopic adenoidectomy was used by El-Badrawy and Abdel-Aziz [12]; although the technique is simple, it needs special instruments that may be not available in the theater.…”
Section: Introductionmentioning
confidence: 99%